Economic implications of ddPCR and NGS-based noninvasive prenatal testing for fetal aneuploidy screening - Mittal, Amit Kumar; Shekhawat, Dolat Singh; Patel, Mamta; Singh, Pratibha; Singh, Kuldeep (International Journal of Public Health Science (IJPHS), 2024)
Noninvasive prenatal testing (NIPT) heralds a transformative era in prenatal care, revolutionizing fetal health assessment. The recent adoption of aneuploidy screening signifies a significant advancement in prenatal genetic care in India. The current study aimed to assess the cost-effectiveness of ddPCR-based NIPT for detecting chromosome aneuploidies, comparing it with the next-generation sequencing (NGS) platform. This study adopts a laboratory-based observational approach to investigate the cost implications of NIPT for trisomies 13, 18, and 21 using ddPCR and NGS technologies. A meticulously designed cost analysis methodology was employed, adhering to established standards. The yearly capital and operational costs of NIPT were calculated with precision, focusing on the specific methods associated with ddPCR and NGS. The calculated annual capital and operating costs for NIPT using the ddPCR were $16,411 and $246,540 while those using the NGS platform were $91,440 and $250,560, respectively. The total cost of NIPT using ddPCR for 2,400 tests was $262,951, with an estimated cost per test of $110. In contrast, the total cost of NIPT using the NGS platform for 600 tests was $342,000, resulting in an estimated cost per test of $570. The ddPCR is five times more cost-effective. Moreover, it exhibits a fourfold reduction in time expenditure, attributable to streamlined procedures and does not require a complex bioinformatics analysis compared to the NGS. Moreover, this preliminary outcome on cost analysis for NIPT using ddPCR, as opposed to the NGS platform, can be extended to the health technology assessment (HTA) perspective for prenatal screening programs.